Analysis of The Principle of Freedom of Contract In A Work Agreement Containing Non-Competition Clause - Wahyu Tri Yuliana; N.Santy Parnasari (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2020)
Legal relations between workers and companies is inseparable from work agreements. The formation of work agreements between workers and companies must be in accordance with legal requirements and agreement principles. One of the principles used is the principle of freedom of contract as stipulated in Article 1338 Burgelijk Wetboek voor Indonesie (BW). However, the existence of a company that includes a non-competition clause in a work agreement is one of the preventive measures in order to maintain the company's trade secrets which results in limited space for workers and is contrary to several laws and regulations. This study aims to analyze the principle of freedom of contract in a work agreement that contains a non-competition clause. This is a normative juridical method research with a comparative approach to compare laws and regulations governing the principle of freedom in contracting with non-competition clause of the work agreement. Analytical descriptive is used to describe the principle of freedom in contract with the theory of non-competition clause, thus, this research is qualitative research. However, the principle of freedom of contract cannot be interpreted as absolutely free, the essence must be a balance between the rights and obligations of workers and companies in work agreements. In the inclusion of non-competition clauses, it can limit the movement of workers to find work and this clause basically contradicts several regulations relating to the right to get a job. Work agreement containing non-competition clause does not meet the legal agreement. Therefore, it can be canceled by law based on the provisions of Article 52 paragraph (3) of Law Number 13 Year 2003 concerning Labor.